Atividade física e saúde: análise do projeto social de judô - Lage, Victor (2015)
Introduction: practice of physical activity and its relationship with health maintenance, health promotion and quality of life are frequently researched in several areas of health sciences. Recent studies have suggested martial arts as a resource for health promotion and generated questions about its impact on people global functioning. Ample dissemination of those corporal practices indicates the need of more investigations about its characteristics. Since 1993, the São José do Rio Preto (SP) Municipal Secretary of Sports and Leisure maintains a partnership with the Judo´s Social Project, with the participation of low income children and adolescents from 17 training centers. Objective: to investigate global psychosocial functioning of Judo´s Social Project children and adolescents from August/2011 to December/2011. Three articles were written after data collection and analysis. The first has summarized publications from April/2004 to April/2014 analyzing the relationship between martial arts, fights and children and adolescents mental health. Articles were searched in health databases for articles, dissertations and theses from: Pubmed, Scielo, Bireme, Periódicos Capes, Brazilian Digital Library of Theses and Dissertations (BDTD), and bank of dissertations and theses PUC, UEL, UNESP, UNICAMP, UNIFESP, UnB e USP. Studies with children and adolescents (6 to 18 years) were selected based on inclusion and exclusion criteria (language, year of publication, participant’s age, theme and repeated studies). Twenty five studies were selected. Results from this review suggest positive associations when martial arts are traditionally oriented and negatively when associated with high performance sport. Evidences and longitudinal studies are still necessary to obtain consistent data allowing the prescription of martial arts for education and health. The second article investigated depressive symptoms among 904 children and adolescents who practice judo, 563 males, 7 to 17 years old (9.9± 2.2) who filled the Children´s Depression Inventory (CDI) during lessons, in judo rooms, with the presence of researchers and teacher responsible for the lessons. Scores ≥ 17 points were classified as "presence of depressive symptoms" The inclusion criteria for participants were: consent of the participants and responsible, aged between 7 and 17 years, registration in basic education and social project judo. All participants in this age group were invited to participate in the survey, with rejection rate estimated at 5%. The scores obtained in the CDI were compared by gender "Male" x "Female". Participants were also grouped into "Younger" (7-12 years) and "Older" (13-17 years) and compared again by sex. Data collection occurred from August to December 2011, with the approval by the Ethics Committee (CEP/FAMERP, 138/2011). Males had lower scores when compared to females, but without statistical significance for age, and this data is similar to national literature on the topic. The third article analyzed the behavioral profile of 308 teenagers, 183 boys, 11 to 18 years old (12.4 ±1.54), who filled the Youth Self Report (YSR/2001). The eight syndrome-scales and six clusters DSM-IV oriented were analyzed according to the Brazilian validation study norms. In the analysis of the scores, the borderline range was grouped with the clinical range in order to minimize the occurrence of false negative. It was also analyzed the raw scores (mean and standard deviation), comparing them to the study of Brazilian validation study. Results: 308 participants, 183 boys and 125 girls, aged between 11 and 18 years (12.4 ± 1.54). Scores on the scale of anxiety and depression were significantly higher for girls (p = 0.0431). The scales oriented for DSM-IV, the girls also had higher anxiety scores (p = 0.0011). Boys had significantly higher scores for violation of rules (p = 0.0020). Oriented scale for DSM-IV, conduct problems (p = 0.0085) and externalization scale (p = 0.0315) were more frequent among boys. In the scale of total problems, 34.4% (N = 106) of the sample was considered clinical in average scores. Among girls, 24.8% (N = 31) were considered clinical and between the boys 41% (N = 75). Participants achieved clinical scores less frequently than the data from the Brazilian standard. Internalizing problems (anxiety and depression) were more common for girls and externalizing (violation of rules and conduct problems) for boys. Younger children showed more somatic complaints and problems than older. Conclusion: Martial arts for social projects for children and adolescents must consider instructors, coaches, teachers and professionals participation, assessing ecological and psychological variables, and focus on relationship between participants, families, schools, social agents and councils. It is necessary to understand the multifactorial characteristics of martial arts associated to social projects with children and adolescents. It is also necessary to recognize all variables and their impact on further research and to improve quality of social projects for low income families.